Pengaruh Online Customer Review, Rating dan Deskripsi Terhadap Minat Beli Kamar Sanctoo Suites & Villas Pada TripAdvisor - Adyatma, Prastha; Adinda, Clearesta (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2023)
This research aims to investigate the influence of Online Customer Review, Rating, and Description on the purchase intent of Sanctoo Suites & Villas rooms on the TripAdvisor platform. The methodology employed is quantitative, involving the distribution of questionnaires to TripAdvisor users. The study's findings indicate that, significantly, it is the description that affects purchase intent. In the data analysis, it was discovered that the information conveyed through the description has a stronger positive impact compared to online customer reviews and ratings in influencing the purchase intent of potential guests. An informative and compelling description assists potential guests in forming a better understanding of the experience they can expect when staying at Sanctoo Suites & Villas. These results offer valuable guidance to property owners in optimizing their descriptions to enhance attraction and booking conversion. This research provides important insights into the significance of descriptive information in consumer decision-making in the digital era, particularly in the hospitality industry. The practical implications of these findings suggest that property owners should prioritize improving the quality of their descriptions to capture greater purchase intent from potential guests on the TripAdvisor platform.